Composite resin material as well as preparation method and application thereof
By using composite resin materials, including resin monomers, organic fillers and inorganic fillers, the problems of poor transparency and insufficient affinity of existing dental pallet materials are solved, and a dental pallet material with high transparency and good hydrophilicity are achieved.
Patent Information
- Application Number
- CN202411272446.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-03-25
AI Technical Summary
The transparency of existing dental pallet materials is poor, and the dental impression and morphology cannot be observed, and the affinity with some impression materials is also poor.
Pallet materials are prepared by mixing and initiating curing by using composite resin materials, including resin monomers, organic fillers (such as polymethyl methacrylate particles and polyethyl methacrylate particles) and inorganic fillers.
The transparency and hydrophilicity of the composite resin material are improved, making it easy to observe the internal conditions of the oral cavity during use, and used with different impression materials, with good mechanical properties and hydrophilicity.
Smart Images

Figure CN119684738A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of dental materials, and in particular to a composite resin material and a preparation method and application thereof. Background Art
[0002] Dental personalized trays are trays that are customized to meet the specific needs of the patient's oral anatomy and are mainly used in the impression process of full dentures. The edge line of the personalized tray needs to be determined according to each person's oral anatomy, but the tray material is mostly made of red wax or acrylic resin material, which has poor transparency and cannot be observed during use. The dental impression and morphology, and the tray has poor affinity with some impression materials. Summary of the invention
[0003] Based on this, an embodiment of the present application provides a composite resin material with high transparency and good affinity, and a preparation method and application thereof.
[0004] In a first aspect, the present application provides a composite resin material, wherein raw materials of the composite resin material include: a resin monomer, an organic filler, an inorganic filler and an initiator, wherein the organic filler includes polymethyl methacrylate particles and polyethyl methacrylate particles.
[0005] In some embodiments, the number average molecular weight of the polymethyl methacrylate particles is 100,000 to 1,000,000, the light transmittance is ≥ 60%, and the volume average particle size Dv50 is 0.5 μm to 50 μm.
[0006] In some embodiments, the number average molecular weight of the polyethyl methacrylate particles is 100,000 to 1,000,000, the light transmittance is ≥ 60%, and the volume average particle size Dv50 is 0.5 μm to 50 μm.
[0007] In some embodiments, the mass ratio of the polymethyl methacrylate particles to the polyethyl methacrylate particles is (1-5):1.
[0008] In some embodiments, the mass proportion of spherical particles in the organic filler is ≥50%.
[0009] In some embodiments, the polyethyl methacrylate particles include modified polyethyl methacrylate particles.
[0010] Optionally, the modified groups contained in the modified polyethyl methacrylate particles include at least one of hydroxyl groups, epoxy groups and carboxyl groups.
[0011] Optionally, the mass proportion of the modified groups contained in the modified polyethyl methacrylate particles is 0-10%. In some embodiments, the inorganic filler includes a first inorganic filler and a second inorganic filler.
[0012] Optionally, the volume average particle size Dv50 of the first inorganic filler is 50 μm to 100 μm.
[0013] Optionally, the volume average particle size Dv50 of the second inorganic filler is 1 nm to 100 nm.
[0014] Optionally, the first inorganic filler includes at least one of quartz powder and glass powder.
[0015] Optionally, the second inorganic filler includes white carbon black.
[0016] In some embodiments, the mass proportion of spherical particles in the inorganic filler is ≥50%.
[0017] In some embodiments, the light transmittance of the inorganic filler is ≥ 80%.
[0018] In some embodiments, the mass proportion of the resin monomer in the composite resin material is 20% to 50%.
[0019] In some embodiments, the mass proportion of the organic filler in the composite resin material is 30% to 50%.
[0020] In some embodiments, the mass proportion of the inorganic filler in the composite resin material is 15% to 35%.
[0021] In some embodiments, the mass proportion of the initiator in the composite resin material is 0% to 1%.
[0022] In some embodiments, the resin monomer includes a first resin monomer.
[0023] Optionally, the first resin monomer contains at least one polyacrylate functional group; further optionally, the first resin monomer includes at least one of bisphenol A propylene glycol dimethacrylate, triethylene glycol dimethacrylate, methyl methacrylate, hydroxyethyl methacrylate, dimethacrylate carbamate, bisphenol A glycidyl dimethacrylate, polyethylene glycol dimethacrylate and ethylene glycol dimethacrylate.
[0024] In some embodiments, the resin monomer further includes a second resin monomer.
[0025] Optionally, the second resin monomer includes at least one of hydroxyethyl acrylate, isobornyl acrylate, tripropylene glycol diacrylate, acryloyl morpholine, tripropylene glycol diacrylate and tetrahydrofuran acrylate.
[0026] In some embodiments, the composite resin material further includes an auxiliary agent.
[0027] Optionally, the auxiliary agent includes at least one of a colorant and a plasticizer; further optionally, the plasticizer includes at least one of di(2-ethylhexyl) phthalate, di(2-ethylhexyl) adipate, di(2-ethylhexyl) sebacate, 1,6-dimethylacrylate and polyethylene glycol acrylate.
[0028] Optionally, the mass proportion of the auxiliary agent in the composite resin material is 0% to 10%.
[0029] In a second aspect, the present application provides a method for preparing a composite resin material, the preparation method comprising:
[0030] The composite resin material is prepared by mixing resin monomers, organic fillers, inorganic fillers and initiators, wherein the organic fillers include polymethyl methacrylate particles and polyethyl methacrylate particles.
[0031] In a third aspect, the present application provides a use of a composite resin material prepared by the composite resin material described in the first aspect or the method for preparing a composite resin material described in the second aspect in preparing a dental tray.
[0032] Compared with the traditional technology, this application has at least the following beneficial effects:
[0033] The composite resin material of the present application is matched with an organic filler and an inorganic filler, wherein the organic filler is a combination of polymethyl methacrylate particles and polyethyl methacrylate particles, the organic filler has good dispersibility in the composite resin material, the polymethyl methacrylate particles have high light transmittance and high hardness, and the polyethyl methacrylate particles have good ductility, which not only improves the operability of the composite resin material during use, but also improves the transparency and hydrophilicity of the composite resin material, making it easy to observe the internal conditions of the oral cavity during use, and can be used in combination with different impression materials. The composite resin of the present application can still maintain transparency after initiation and curing, and has good mechanical properties and hydrophilicity. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is an electron microscope image of the composite resin material prepared in Example 1 of the present application;
[0035] Figure 2 This is a test result diagram of the composite resin material prepared in Example 1 of the present application after curing;
[0036] Figure 3 This is a test result diagram of the composite resin material prepared in Example 3 of the present application after curing;
[0037] Figure 4 This is a test result diagram of the composite resin material prepared in Comparative Example 1 of the present application after curing;
[0038] Figure 5 This is the elemental analysis diagram of the spherical quartz powder in Example 1 of the present application. DETAILED DESCRIPTION
[0039] Below in conjunction with the embodiments and examples, the present application is further described in detail. These embodiments and examples are only used to illustrate the present application and are not used to limit the scope of the present application. The purpose of providing these embodiments and examples is to make the understanding of the disclosure of the present application more thorough and comprehensive. It should also be understood that the present application can be implemented in many different forms, and is not limited to the embodiments and examples described herein. Those skilled in the art can make various changes or modifications without violating the connotation of the present application, and the equivalent form obtained also falls within the protection scope of the present application. In addition, in the description below, a large number of specific details are given in order to provide a more comprehensive understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0041] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.
[0042] In this application, the terms "first", "second", etc. in "the first aspect", "the second aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0043] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0044] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for a broad range of quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.
[0045] All documents mentioned in this application are cited as references in this application, just as each document is cited as reference separately. Unless they conflict with the application purpose and / or technical solution of this application, the cited documents involved in this application are cited with all contents and all purposes. When the cited documents are involved in this application, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the cited documents are involved in this application, the examples and preferred methods of the cited relevant technical features can also be incorporated into this application as references, but are limited to the implementation of this application. It should be understood that when the cited content conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.
[0046] In traditional technology, tray materials are red wax sheets or acrylic resin materials. Among them, red wax sheets have poor transparency and dental impressions and morphology cannot be observed during use; although acrylic resin materials have good durability and detail reproduction capabilities, they are poor in operability and have poor affinity with some impression materials.
[0047] In a first aspect, the present application provides a composite resin material, wherein raw materials of the composite resin material include: a resin monomer, an organic filler, an inorganic filler and an initiator, wherein the organic filler includes polymethyl methacrylate (PMMA) particles and polyethyl methacrylate (PEMA) particles.
[0048] The composite resin material of the present application is matched with an organic filler and an inorganic filler, wherein the organic filler is a combination of polymethyl methacrylate particles and polyethyl methacrylate particles. The organic filler has good dispersibility, high light transmittance and high hardness in the composite resin material, and the polyethyl methacrylate particles have good ductility, which not only improves the operability of the composite resin material during use, but also improves the transparency and hydrophilicity of the composite resin material, making it easy to observe the internal conditions of the oral cavity during use, and can be used in combination with different impression materials. The composite resin of the present application can still maintain transparency after initiation and curing, and has good mechanical properties and hydrophilicity.
[0049] It is understandable that the composite resin material of the present application is operable during use and can be adjusted in shape according to the mold. When the shape adjustment is completed, it can be cured by initiating curing, during which the resin monomers are cross-linked and cured to obtain a tray.
[0050] In some embodiments, the number average molecular weight of the polymethyl methacrylate particles is 100,000 to 1,000,000, for example, 100,000, 200,000, 300,000, 400,000, 500,000, 600,000, 700,000, 800,000, 900,000 or 1,000,000.
[0051] In some embodiments, the light transmittance of the polymethyl methacrylate particles is ≥ 60%, for example, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 99%.
[0052] In some embodiments, the volume average particle size Dv50 of the polymethyl methacrylate particles is 0.5 μm to 50 μm. For example, it can be 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm. It can be 1 μm to 10 μm.
[0053] In some embodiments, the number average molecular weight of the polyethyl methacrylate particles is 100,000 to 1,000,000, for example, 100,000, 200,000, 300,000, 400,000, 500,000, 600,000, 700,000, 800,000, 900,000 or 1,000,000.
[0054] The present application selects the number average molecular weight of the polymethyl methacrylate particles and the number average molecular weight of the polyethyl methacrylate particles as above, which effectively ensures that the organic filler swells or dissolves in the resin monomer, improves the affinity between the resin monomer and the organic filler, and can improve the mechanical strength of the material after initiation of curing, especially the flexibility and strength.
[0055] In some embodiments, the light transmittance of the polyethyl methacrylate particles is ≥ 60%, for example, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 99%.
[0056] In some embodiments, the volume average particle size Dv50 of the polyethyl methacrylate particles is 0.5 μm to 50 μm, for example, 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, and can be 1 μm to 10 μm.
[0057] The particle size of the polymethyl methacrylate particles and the particle size of the polyethyl methacrylate particles are selected as above in the present application to ensure the swelling and dissolution speed of the organic filler and improve the processing efficiency. If the particle size is relatively small, the material may be too fluffy and not conducive to processing; if the particle size is relatively large, the particle surface area is small, the swelling and dissolution speed may be slow, and the processing efficiency is low.
[0058] In some embodiments, the mass ratio of the polymethyl methacrylate particles to the polyethyl methacrylate particles is (1-5):1, for example, 1.0:1, 1.5:1, 2.0:1, 2.5:1, 3.0:1, 3.5:1, 4.0:1, 4.5:1 or 5.0:1. The mass ratio of the polymethyl methacrylate particles to the polyethyl methacrylate particles selected in the present application can take into account the strength, light transmittance and flexibility of the material, and avoid the material being brittle and easy to break after initiation of curing.
[0059] In some embodiments, the mass proportion of spherical particles in the organic filler is ≥50%, for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%. In the present application, the organic filler is selected from spherical particles, which have a good infiltration effect with the resin monomer and are conducive to filling during the processing. The morphology of ordinary PMMA particles is mostly irregular and irregular, and the infiltration speed with the resin monomer is extremely slow.
[0060] It is understood that spherical particles refer to particles with a sphericity of ≥ 80%, which can be approximately spherical or completely spherical.
[0061] In some embodiments, the polyethyl methacrylate particles include modified polyethyl methacrylate particles.
[0062] Optionally, the modified group contained in the modified polyethyl methacrylate particles includes at least one of a hydroxyl group, an epoxy group and a carboxyl group. Optionally, the modified group includes a carboxyl group. The modified polyethyl methacrylate particles used in the present application can accelerate the infiltration speed of the resin monomer, which can not only improve the processing synergy with the polymethyl methacrylate particles, stabilize the performance of the composite resin material, but also improve the ductility and operability of the composite resin material.
[0063] Optionally, the mass proportion of the modified groups contained in the modified polyethyl methacrylate particles is 0-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. In some embodiments, the inorganic filler includes a first inorganic filler and a second inorganic filler.
[0064] Optionally, the volume average particle size Dv50 of the first inorganic filler is 50μm~100μm, for example, it can be 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm or 100μm. The present application selects the particle size of the first inorganic filler as above to improve the flow state and thixotropic effect of the composite resin material, ensure the operability of the composite resin material during the impression process, and improve the adhesion to the instrument and hand, and can improve the impression accuracy and affinity with the impression material. If the particle size is relatively small, it may cause the composite resin material to have high fluidity, which is not conducive to the impression operation; if the particle size is relatively large, it may affect the accuracy of the impression tray, and the affinity with the impression material will deteriorate.
[0065] Optionally, the volume average particle size Dv50 of the second inorganic filler is 1 nm to 100 nm, for example, 1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm.
[0066] The present application selects the particle size of the second inorganic filler as described above so that the second inorganic filler can be fully integrated into the first filler, further improving operability, impression accuracy and affinity with the impression material.
[0067] Optionally, the first inorganic filler includes at least one of quartz powder and glass powder. For example, the glass powder includes borosilicate glass powder.
[0068] Optionally, the second inorganic filler includes white carbon black.
[0069] Optionally, the mass ratio of the first inorganic filler to the second inorganic filler is (0.9-10):1, for example, 0.9:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1. For example, the inorganic filler includes white carbon black (i.e., fumed silica) and spherical quartz powder. The present application selects the mass ratio of the first inorganic filler to the second inorganic filler as above to effectively ensure the strength, operability and affinity of the composite resin material.
[0070] In some embodiments, the mass proportion of spherical particles in the inorganic filler is ≥50%, for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%. In the present application, the inorganic filler uses spherical particles. Spherical particles not only have a large filling amount, but also have a better wetting effect with the resin monomer. In addition, larger spherical particles have good light transmittance and uniform light transmission. The morphology of the particles of ordinary inorganic fillers is mostly angular, with poor light transmittance and uneven light transmission.
[0071] In some embodiments, the light transmittance of the inorganic filler is ≥ 80%, for example, it may be 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98% or 99%.
[0072] In some embodiments, the inorganic filler contains a doping element. Optionally, the doping element includes at least one of Ca, Al, Mg and Na. The inorganic filler of the present application contains a doping element, which can further improve the light transmittance of the inorganic filler, thereby improving the transparency of the resin, and the use of light-induced curing can effectively improve the curing effect.
[0073] In some embodiments, the mass proportion of the resin monomer in the composite resin material is 20% to 50%, for example, 20%, 23%, 26%, 29%, 32%, 35%, 38%, 41%, 44%, 47% or 50%. It can be 20% to 40%.
[0074] In some embodiments, the mass proportion of the organic filler in the composite resin material is 30% to 50%, for example, it can be 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48% or 50%.
[0075] In some embodiments, the mass proportion of the inorganic filler in the composite resin material is 15% to 35%, for example, 15%, 17%, 19%, 21%, 23%, 25%, 27%, 29%, 31%, 33% or 35%.
[0076] In some embodiments, the mass proportion of the initiator in the composite resin material is 0% to 1%, for example, it may be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1.0%. It may be 0% to 0.3%.
[0077] In some embodiments, the resin monomer includes a first resin monomer.
[0078] Optionally, the first resin monomer contains at least one polyacrylate functional group.
[0079] Further optionally, the first resin monomer includes at least one of bisphenol A propylene glycol dimethacrylate (BisGMA), triethylene glycol dimethacrylate (TEGDMA), methyl methacrylate (MMA), hydroxyethyl methacrylate (HEMA), dimethacrylate urethane (UDMA), bisphenol A dimethacrylate glycidyl ester (BisEMA), polyethylene glycol dimethacrylate (PEGDMA) and ethylene glycol dimethacrylate (EGDMA). Further optional is bisphenol A propylene glycol dimethacrylate (BisGMA), dimethacrylate urethane (UDMA) and triethylene glycol dimethacrylate (TEGDMA).
[0080] In some embodiments, the resin monomer further comprises a second resin monomer. In the present application, the addition of the second resin monomer can improve the viscosity and wettability of the composite resin material.
[0081] Optionally, the second resin monomer includes at least one of hydroxyethyl acrylate (HEA), isobornyl acrylate (IBOA), tripropylene glycol diacrylate (TPGDA), acryloyl morpholine (ACMO), tripropylene glycol diacrylate (TPGDA), and tetrahydrofuran acrylate (THFA).
[0082] In some embodiments, the initiator comprises a photoinitiator.
[0083] Optionally, the photoinitiator includes camphorquinone, benzoin and derivatives, benzil initiators, alkyl phenone initiators, acyl phosphorus oxides, benzophenone initiators and thioxanthone initiators. For example, benzoin and derivatives include at least one of benzoin, benzoin dimethyl ether, benzoin ethyl ether, benzoin isopropyl ether and benzoin butyl ether. Benzil initiators include at least one of diphenyl acetophenone and α, α-dimethoxy-α-phenyl acetophenone. Alkyl phenone initiators include at least one of α, α-diethoxyacetophenone, α-hydroxyalkyl phenone and α-aminoalkyl phenone. Acyl phosphorus oxides include at least one of aromatic phosphine oxides and dibenzoylphenyl phosphine oxides. Benzophenone initiators include at least one of benzophenone, 2,4-dihydroxybenzophenone and Michler's ketone. Thioxanthone initiators include at least one of thiopropoxythioxanthone and isopropylthioxanthone.
[0084] Optionally, the photoinitiator includes a cationic photoinitiator. For example, the cationic photoinitiator includes at least one of diaryliodonium salt, triaryliodonium salt, alkylliodonium salt and cumene ferrocenium hexafluorophosphate.
[0085] In some embodiments, the photoinitiator includes camphorquinone, 2,4,6-trimethylbenzoyldiphenoxyphosphine (TPO), and a cationic photoinitiator.
[0086] In some embodiments, the composite resin material further includes an auxiliary agent.
[0087] Optionally, the auxiliary agent includes at least one of a colorant and a plasticizer; further optionally, the plasticizer includes at least one of di(2-ethylhexyl) phthalate (DOP), di(2-ethylhexyl) adipate (DOA), di(2-ethylhexyl) sebacate (DOS), 1,6-dimethylacrylate (HDDMA) and polyethylene glycol acrylate (PEGDMA). Optionally, the plasticizer includes HDDMA and PEGDMA. Adding a plasticizer in the present application can improve the operability of the composite resin material during use.
[0088] Optionally, the mass proportion of the auxiliary agent in the composite resin material is 0% to 10%, for example, 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. Optionally, it can be 2% to 8%.
[0089] In some embodiments, the colorant includes at least one of red iron oxide and yellow iron oxide. It is understood that different colorants can be selected according to different coloring requirements.
[0090] A second aspect of the present application provides a method for preparing a composite resin material, the preparation method comprising:
[0091] The composite resin material is prepared by mixing resin monomers, organic fillers, inorganic fillers and initiators, wherein the organic fillers include polymethyl methacrylate particles and polyethyl methacrylate particles.
[0092] In some embodiments, the stirring speed during the mixing process is 5 rpm to 30 rpm, and can be 10 rpm to 20 rpm.
[0093] In some embodiments, the mixing time is 1 h to 3 h.
[0094] In some embodiments, the temperature during mixing is 50°C to 70°C.
[0095] A third aspect of the present application provides a use of a composite resin material prepared by the composite resin material according to the first aspect or the method for preparing a composite resin material according to the second aspect in preparing a dental tray.
[0096] In some embodiments, a method for preparing a dental tray comprises:
[0097] The composite resin materials are mixed and then molded; after molding, they are cured to obtain a dental tray.
[0098] The embodiments of the present application will be described in detail below in conjunction with examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are preferably referred to the guidance provided in the present application, and can also be based on the experimental manual or normal conditions in this area, can also be based on the conditions recommended by the manufacturer, or refer to experimental methods known in the art.
[0099] Example 1
[0100] Weigh the resin monomer, organic filler, inorganic filler, initiator and auxiliary agent according to the mass fraction, including:
[0101] Bis-GMA 28 parts;
[0102] UDMA 15 parts;
[0103] TEGDMA 5 parts;
[0104] 10 parts of spherical PMMA particles;
[0105] 20 parts of modified spherical PEMA particles;
[0106] 1.4 parts of white carbon black;
[0107] 20 parts of spherical quartz powder;
[0108] 0.5 parts of camphorquinone; and
[0109] 0.1 parts of diaryliodonium salt.
[0110] Among them, the number average molecular weight of spherical PMMA particles is 300,000, the light transmittance is 90%, and the volume average particle size Dv50 is 5μm; the modified spherical PEMA particles are modified by carboxyl groups, the carboxyl groups account for 5% of the mass of the modified spherical PEMA particles, the number average molecular weight is 50,000, the light transmittance is 90%, and the volume average particle size Dv50 is 5μm. The volume average particle size Dv50 of white carbon black is 20nm; the volume average particle size Dv50 of spherical quartz powder is 85μm, the light transmittance is 80%, and the elemental analysis of spherical quartz powder is as follows Figure 5 shown.
[0111] The above resin monomer, organic filler, inorganic filler, initiator and auxiliary agent are mixed in a double planetary mixer to obtain Figure 1 The resin composite material shown, wherein the stirring speed is 15 rpm, the time is 2 h, and the temperature is 60 °C.
[0112] Example 2
[0113] The composite resin material is prepared according to the method of Example 1, except that the raw materials include:
[0114] Bis-GMA 20 parts;
[0115] UDMA 10 parts;
[0116] TEGDMA 5 parts;
[0117] 10 parts of spherical PMMA particles;
[0118] 20 parts of modified spherical PEMA particles;
[0119] 5 parts of white carbon black;
[0120] 29.3 parts of spherical quartz powder;
[0121] Camphorquinone 0.2 parts;
[0122] TPO 0.4 parts; and,
[0123] 0.1 parts of diaryliodonium salt.
[0124] Example 3
[0125] The composite resin material is prepared according to the method of Example 1, except that the raw materials include:
[0126] Bis-GMA 20 parts;
[0127] UDMA 10 parts;
[0128] TEGDMA 5 parts;
[0129] 30 parts of spherical PMMA particles;
[0130] 10 parts of modified spherical PEMA particles;
[0131] 3 parts of white carbon black;
[0132] 21.37 parts of spherical quartz powder;
[0133] TPO 0.5 parts;
[0134] 0.1 part of diaryliodonium salt;
[0135] 0.02 parts of red iron oxide; and
[0136] 0.01 part of iron oxide yellow.
[0137] Example 4
[0138] The composite resin material is prepared according to the method of Example 1, except that the raw materials include:
[0139] Bis-GMA 10 parts;
[0140] UDMA 10 parts;
[0141] TEGDMA 5 parts;
[0142] 30 parts of spherical PMMA particles;
[0143] 10 parts of modified spherical PEMA particles;
[0144] 21.16 parts of spherical quartz powder;
[0145] 3 parts of angular quartz powder;
[0146] 0.5 part of camphorquinone;
[0147] TPO 0.2 parts;
[0148] 0.1 parts of diaryliodonium salt; and
[0149] 0.04 parts of red iron oxide.
[0150] The volume average particle size Dv50 of the angular quartz powder is 50 μm, and the surface of the angular quartz powder has multiple edges and corners.
[0151] Example 5
[0152] The composite resin material is prepared according to the method of Example 1, except that the raw materials include:
[0153] Bis-GMA 15 parts;
[0154] UDMA 5 parts;
[0155] 3 parts of isobornyl acrylate;
[0156] 20 parts of spherical PMMA particles;
[0157] 25 parts of spherical PEMA particles;
[0158] 11.3 parts of white carbon black;
[0159] 20 parts of spherical quartz powder;
[0160] 0.1 part of 1,6-dimethacrylate;
[0161] 0.5 parts of camphorquinone; and
[0162] 0.1 parts of diaryliodonium salt.
[0163] Among them, the number average molecular weight of spherical PMMA particles is 100,000, the transmittance is 90%, and the volume average particle size Dv50 is 0.5μm; the number average molecular weight of spherical PEMA particles is 1 million, the transmittance is 60%, and the volume average particle size Dv50 is 50μm; the volume average particle size Dv50 of spherical quartz powder is 100μm, and the transmittance is 60%.
[0164] Example 6
[0165] The composite resin material is prepared according to the method of Example 1, except that the raw materials include:
[0166] Bis-GMA 20 parts;
[0167] UDMA 20 parts;
[0168] 10 parts of spherical PMMA particles;
[0169] 25 parts of spherical PEMA particles;
[0170] 14.3 parts of white carbon black;
[0171] 10 parts of spherical quartz powder;
[0172] 0.1 part of 1,6-dimethacrylate;
[0173] 0.5 parts of camphorquinone; and
[0174] 0.1 parts of diaryliodonium salt.
[0175] Among them, the number average molecular weight of spherical PMMA particles is 100,000, the transmittance is 90%, and the volume average particle size Dv50 is 0.5μm; the number average molecular weight of spherical PEMA particles is 1 million, the transmittance is 60%, and the volume average particle size Dv50 is 50μm; the volume average particle size Dv50 of spherical quartz powder is 100μm, and the transmittance is 60%.
[0176] Example 7
[0177] The composite resin material was prepared according to the method of Example 1, except that the modified spherical PEMA particles were replaced with an equal mass fraction of common modified PEMA particles, and the particle morphology of the common modified PEMA particles was angular, and the surface had multiple edges and corners.
[0178] Example 8
[0179] The composite resin material was prepared according to the method of Example 1, except that the volume average particle size Dv50 of the spherical quartz powder was 120 μm.
[0180] Example 9
[0181] The composite resin material was prepared according to the method of Example 1, except that the volume average particle size Dv50 of the spherical quartz powder was 20 μm.
[0182] Comparative Example 1
[0183] The composite resin material is prepared according to the method of Example 1, except that the raw materials include:
[0184] Bis-GMA 10 parts;
[0185] UDMA 5 parts;
[0186] TEGDMA 5 parts;
[0187] 30 parts of ordinary PMMA particles;
[0188] 20 parts of white carbon black;
[0189] 29.07 parts of angular quartz powder;
[0190] 0.5 part of camphorquinone;
[0191] TPO 0.3 parts;
[0192] 0.1 parts of diaryliodonium salt.
[0193] 0.02 parts of red iron oxide; and
[0194] 0.01 part of iron oxide yellow.
[0195] Comparative Example 2
[0196] The composite resin material is prepared according to the method of Example 1, except that the raw materials include:
[0197] Bis-GMA 10 parts;
[0198] UDMA 5 parts;
[0199] TEGDMA 5 parts;
[0200] 30 parts of ordinary PMMA particles;
[0201] 20 parts of white carbon black;
[0202] 5 parts of spherical quartz powder;
[0203] 24.1 parts of angular quartz powder;
[0204] 0.5 part of camphorquinone;
[0205] TPO 0.3 parts; and,
[0206] 0.1 parts of diaryliodonium salt.
[0207] Comparative Example 3
[0208] The composite resin material was prepared according to the method of Example 1, except that the spherical PMMA particles were replaced by modified spherical PEMA particles in equal parts by mass.
[0209] Comparative Example 4
[0210] The composite resin material was prepared according to the method of Example 1, except that the modified spherical PEMA particles were replaced by spherical PMMA particles of equal mass fraction.
[0211] The composite resin material prepared in the above examples and comparative examples is subjected to initiation and curing, comprising:
[0212] The composite resin was initiated by visible light with a wavelength of 435nm and an irradiation intensity of ≥600mW / cm².
[0213] The performance tests of the materials after initiation and curing of the above embodiments and comparative examples were carried out, including:
[0214] Transmittance: The transmittance was measured using an ultraviolet spectrophotometer, where the thickness of the test sample was 0.5 mm and the wavelength of the test light source was 435 nm. The test results are shown in Table 1.
[0215] Bending strength and compressive strength: The cured material was prepared into bending and compression specimens. The bending specimen size was 2 mm × 2 mm × 2 mm, and the compression specimen size was a cylinder with a diameter of 2 mm and a height of 4 mm. The test results are shown in Table 1.
[0216] Contact angle: The hydrophilicity of the cured material was tested using a contact angle tester. The test results of Example 1 are as follows: Figure 2 As shown, the test results of Example 3 are as follows Figure 3 As shown, the test results of Comparative Example 1 are as follows Figure 4 The test results are shown in Table 1.
[0217] Table 1
[0218]
[0219] From the above table we can see that:
[0220] (1) Compared with Example 7, it can be seen that the present application controls the proportion of spherical particles in the organic filler, the spherical particles have a good wetting effect with the resin monomer, and are conducive to filling during the processing, increasing the interfacial bonding ability of the organic filler, causing the tray to have high strength and flexibility after curing, and the processing efficiency is high.
[0221] (2) Compared with Examples 8-9, it can be seen that the present application controls the particle size of the first inorganic filler, improves the flow state and thixotropic effect of the composite resin material, ensures the operability of the composite resin material during the impression process, and improves the adhesion to instruments and hands, which can improve the impression accuracy and affinity with the impression material. The material has high light transmittance and compressive strength.
[0222] (3) Compared with Comparative Examples 1-4, it can be seen that the composite resin material of the present application is formulated with organic fillers and inorganic fillers, wherein the organic filler is a combination of polymethyl methacrylate particles and polyethyl methacrylate particles. The organic filler has good dispersibility, high light transmittance and high hardness in the composite resin material, which not only improves the operability of the composite resin material during use, but also improves the transparency and hydrophilicity of the composite resin material, making it easy to observe the internal conditions of the oral cavity during use, and can be used in combination with different impression materials. The composite resin of the present application can still maintain transparency after initiation and curing, and has good mechanical properties and hydrophilicity.
[0223] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0224] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the application. It should be noted that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A composite resin material, characterized in that: The raw materials of the composite resin material include: resin monomer, organic filler, inorganic filler and initiator, and the organic filler includes polymethyl methacrylate particles and polyethyl methacrylate particles.
2. The composite resin material according to claim 1, characterized in that The organic filler satisfies at least one of the following conditions: (1) The number average molecular weight of the polymethyl methacrylate particles is 100,000 to 1,000,000, the light transmittance is ≥ 60%, and the volume average particle size Dv50 is 0.5 μm to 50 μm; (2) The polyethyl methacrylate particles have a number average molecular weight of 100,000 to 1,000,000, a light transmittance of ≥ 60%, and a volume average particle size Dv50 of 0.5 μm to 50 μm; (3) The mass ratio of the polymethyl methacrylate particles to the polyethyl methacrylate particles is (1-5):1; (4) The mass proportion of spherical particles in the organic filler is ≥50%.
3. The composite resin material according to claim 1, characterized in that The polyethyl methacrylate particles include modified polyethyl methacrylate particles; Optionally, the modified groups contained in the modified polyethyl methacrylate particles include at least one of a hydroxyl group, an epoxy group and a carboxyl group; Optionally, the mass proportion of the modified groups contained in the modified polyethyl methacrylate particles is 0-10%.
4. The composite resin material according to claim 1, characterized in that The inorganic filler satisfies at least one of the following conditions: (1) The inorganic filler includes a first inorganic filler and a second inorganic filler; Optionally, the volume average particle size Dv50 of the first inorganic filler is 50 μm to 100 μm; Optionally, the volume average particle size Dv50 of the second inorganic filler is 1 nm to 100 nm; Optionally, the first inorganic filler includes at least one of quartz powder and glass powder; Optionally, the second inorganic filler includes white carbon black; (2) The mass proportion of spherical particles in the inorganic filler is ≥50%; (3) The light transmittance of the inorganic filler is ≥80%.
5. The composite resin material according to claim 1, characterized in that The composite resin material satisfies at least one of the following conditions: (1) The mass proportion of the resin monomer in the composite resin material is 20% to 50%; (2) The mass proportion of the organic filler in the composite resin material is 30% to 50%; (3) The mass proportion of the inorganic filler in the composite resin material is 15% to 35%; (4) The mass proportion of the initiator in the composite resin material is 0% to 1%.
6. The composite resin material according to claim 1, characterized in that The resin monomer includes a first resin monomer; Optionally, the first resin monomer contains at least one polyacrylate functional group; further optionally, the first resin monomer includes at least one of bisphenol A propylene glycol dimethacrylate, triethylene glycol dimethacrylate, methyl methacrylate, hydroxyethyl methacrylate, dimethacrylate carbamate, bisphenol A glycidyl dimethacrylate, polyethylene glycol dimethacrylate and ethylene glycol dimethacrylate.
7. The composite resin material according to claim 6, characterized in that The resin monomer further includes a second resin monomer; Optionally, the second resin monomer includes at least one of hydroxyethyl acrylate, isobornyl acrylate, tripropylene glycol diacrylate, acryloyl morpholine, tripropylene glycol diacrylate and tetrahydrofuran acrylate.
8. The composite resin material according to any one of claims 1 to 7, characterized in that: The composite resin material also includes an auxiliary agent; Optionally, the auxiliary agent includes at least one of a colorant and a plasticizer; further optionally, the plasticizer includes at least one of di(2-ethylhexyl) phthalate, di(2-ethylhexyl) adipate, di(2-ethylhexyl) sebacate, 1,6-dimethylacrylate and polyethylene glycol acrylate; Optionally, the mass proportion of the auxiliary agent in the composite resin material is 0% to 10%.
9. A method for preparing a composite resin material, characterized in that: The preparation method comprises: The composite resin material is prepared by mixing resin monomers, organic fillers, inorganic fillers and initiators, wherein the organic fillers include polymethyl methacrylate particles and polyethyl methacrylate particles.
10. Use of the composite resin material according to any one of claims 1 to 8 or the composite resin material prepared by the method for preparing the composite resin material according to claim 9 in preparing a dental tray.